Rancang Bangun Automatic Washing and Drying System untuk Mesin Pencuci Cylinder Block Motor - Paul Yosua; Dian Budhi Santoso; Arnisa Stefanie (Peneliti.net, 2021)
The process of washing the motor cylinder block is done by manual method, namely by cleaning it using gasoline and then drying it using a dirty cloth. This conventional method has long been used in the washing process of motor cylinder block. So we need a tool that can perform the process of washing motor cylinder block automatically to make it more practical. This study aims to design and design tools that can realize the process of automating the method of washing cylinder block motors. First of all, the concept and workings of the Automatic Washing and Drying System (ADS) tool are determined, then the initial design is made, then determines the materials and components to be used, finally the final design of the tool is designed in detail by placing the components. Differences in the size between the design and the finished product often occur, the biggest difference being 1cm. Testing of several components used was also carried out including a reed switch sensor, a water level float sensor, and a digital thermostat. Reed switches can provide voltage at a maximum distance of 0.6 cm of workpiece. water level float sensor provides voltage at a maximum distance of 0.6 cm of workpiece. The digital thermostat was tested by comparing it to the htc-2 thermometer and there was the largest temperature difference, namely 0.5 ℃.